LAYANAN INFORMASI PUBLIK PEMERINTAH PROVINSI DKI JAKARTA - Erlita, Novi (Universitas Mercu Buana, 2014)
There should be public information management efforts are more balanced. Nottoo forward purely technical aspects to the exclusion of quality information. Therefore, thequality of information that should be the spirit of the information conveyed to the public.Moreover, the form of public information service by the government / public institutions isassociated with it. Jakarta Capital City Government already has a website, but how to designand develop the web as a medium for the provision of government public information? Thisstudy aimed to know, understand and explain the planning and provision of information tothe public conducted by the Public Relations Jakarta Jakarta Provincial Government. Thisresearch used Goverment Communications, Public Relations in Government Institutions,Planning and Development of Public Relation Process, E-Government, Website Managementand Public Information theory. Type of this research is descriptive qualitative by usingmethods of Case Study.The results showed that the Department of Communication,Informatics and Public Relations of Jakarta Capital City Government has entered the stageof planning and preparation for the third time since 1995, which became the backgroundremains the Freedom of Information Law 14 of 2008. The priority program are makeinteractive fitur to public.Seiring berkembangnya teknologi informasi dan komunikasi, ada upayapengelolaan informasi publik yang lebih berimbang. Tidak terlalu mengedepankan aspekteknis belaka sehingga mengabaikan kualitas informasi. Sebab, kualitas informasi ituseharusnya menjadi ruh dari informasi yang disampaikan kepada publik. Apalagi bentuklayanan informasi publik oleh pemerintah/lembaga publik sangat berkaitan dengan haltersebut. Pemerintah Provinsi DKI Jakarta sudah mempunyai web Pemerintah, namunbagaimana merancang dan menyusun web pemerintah ini sebagai media penyediaaninformasi publik? Penelitian ini diarahkan untuk mengetahui, memahami dan menjelaskanperencanaan dan penyusunan penyediaan informasi untuk publik Jakarta yang dilakukan olehHumas Pemerintah Provinsi DKI Jakarta. Kajian teori yang digunakan KomunikasiPemerintahan, Humas Pemerintah, Proses Perencanaan dan Penyusunan Humas, EGovernment,dan Informasi Publik. Jenis penelitian ini adalah deskriptif dengan metodepenelitian yang digunakan Studi Kasus. Hasil penelitian menunjukan bahwa DinasKomunikasi, Informatika dan Kehumasan Pemprov DKI Jakarta sudah memasuki tahapanperencanaan dan penyusunan yang ketiga kalinya semenjak tahun 1995, yang menjadi latarbelakang tetaplah UU KIP No.14 tahun 2008, hanya saja pada tahun yang ditonjolkan adalahpemenuhan informasi publik dan membangun partisipasi public.